2018
DOI: 10.1002/car.2514
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Brain Development: A Discussion of Associated Structural Changes and Negative Psychological Outcomes

Abstract: The effects of traumatic exposure have been researched for many years and studies have shown that the parts of the brain affected by sexually traumatic experiences in childhood are also linked to many physical and psychological problems, such as depression, posttraumatic stress disorder, somatic complaints and suicide. Neuroimaging studies have provided a breadth of evidence that childhood sexual abuse is related to structural changes in the brain. Taken together, childhood sexual abuse affects brain developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…According to Easton (2019), it demonstrated that early disclosure by CSA survivors would be effective in avoiding mental health problems, but only 8.2% of CSA survivors had early disclosure [9]. Most partners of CSA survivors gave very positive feedback after the survivors disclosed their CSA-related experiences, but a large proportion still gave negative feedback, accompanied by condemnation and stigmatization [10]. In addition, more than half of the partners who gave positive feedback were accompanied by condemnation, blaming, and stigmatization.…”
Section: The Responses To Disclosure and Relationship Satisfactionmentioning
confidence: 99%
“…According to Easton (2019), it demonstrated that early disclosure by CSA survivors would be effective in avoiding mental health problems, but only 8.2% of CSA survivors had early disclosure [9]. Most partners of CSA survivors gave very positive feedback after the survivors disclosed their CSA-related experiences, but a large proportion still gave negative feedback, accompanied by condemnation and stigmatization [10]. In addition, more than half of the partners who gave positive feedback were accompanied by condemnation, blaming, and stigmatization.…”
Section: The Responses To Disclosure and Relationship Satisfactionmentioning
confidence: 99%
“…According to the centre of expertise on CSA, there's been increasing awareness of CSA and its impact on survivors in the UK including a focus on mental health and behavioural outcomes (Walsh, Fortier & DiLillo,2010) as an adult's capacity to achieve stability has been linked to experiences of events in childhood (Fergusson & Mullen, 1999). This was strengthened by Edwards (2018) who posited that "CSA affects brain development, leading to differences in brain anatomy and functioning that have lifelong consequences for mental health" (p. 198). Similarly, in the qualitative study of the impact of CSA on both male and female victims, Denov (2004) emphasised on how CSA experiences has led to 'long-term' mental health problems such as 'depression', 'substance abuse', self-harm and other serious behavioural and social difficulties.…”
Section: And Incestmentioning
confidence: 99%
“…These concerns are born out in Damyan Edwards' () review of empirical research on the link between CSA and structural brain abnormalities. Edwards provides a grounded assessment of the strengths and limitations of the field, beginning the review by carefully explaining the research demonstrating the relationship between early trauma and structural changes in the brain.…”
Section: Csa and Brain Impactsmentioning
confidence: 99%